Development of fatigue crack growth model for high pressure natural gas transmission pipelines - Leong, Chih Wei (2018)
Pipelines are the most efficient and advantageous mode of transmission for liquid natural gas. But during manufacturing or during a pipeline’s service life, it incurs damage that can cause dents or cracks on its surface. The severity of such damage is not easy to predict. This is one of the biggest problems faced in transmitting natural gas via transmission pipelines. In this dissertation, a model is developed to understand crack growth under fatigue loading cycles. Iterations are performed on various computational fluid dynamics (CFD) viscous models, and the best model is selected to perform maximum iterations. To replicate real time turbulent load conditions, sinusoidal analogies are used, so as to let us understand the effect of quasiperiodic. This is then combined with the linear damage rule to determine cumulative fatigue damage. The main purpose of this dissertation is to determine and understand the severity of the presence of cracks in transmission pipelines. And to achieve that, simulations are performed using the FE tool. All data generated are presented well in this dissertation in chapters for a better understanding of the approach.